2017
DOI: 10.1073/pnas.1617467114
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide CRISPR screen identifies HNRNPL as a prostate cancer dependency regulating RNA splicing

Abstract: Alternative RNA splicing plays an important role in cancer. To determine which factors involved in RNA processing are essential in prostate cancer, we performed a genome-wide CRISPR/Cas9 knockout screen to identify the genes that are required for prostate cancer growth. Functional annotation defined a set of essential spliceosome and RNA binding protein (RBP) genes, including most notably heterogeneous nuclear ribonucleoprotein L (HNRNPL). We defined the HNRNPL-bound RNA landscape by RNA immunoprecipitation co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
258
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 284 publications
(275 citation statements)
references
References 64 publications
13
258
1
3
Order By: Relevance
“…Consistent with this prediction, hnRNP L has been implicated in oncogenesis through promotion of BCL2 expression in multiple tumor types (Zhou et al, 2016;Lv et al, 2017). Toward this goal, inhibition of hnRNP L itself may be an intriguing avenue for chemotherapy, potentially via blocking protein binding to specific 3 0 UTRs with antisense oligonucleotides (Fei et al, 2017;Shen & Corey, 2018) Additionally, development of compounds for global or transcript-specific NMD enhancement may represent a novel and potentially widely applicable anti-cancer strategy. In contrast, the example of BCL2 provides a case in which increasing transcript sensitivity to NMD may provide therapeutic benefit.…”
Section: Discussionmentioning
confidence: 88%
“…Consistent with this prediction, hnRNP L has been implicated in oncogenesis through promotion of BCL2 expression in multiple tumor types (Zhou et al, 2016;Lv et al, 2017). Toward this goal, inhibition of hnRNP L itself may be an intriguing avenue for chemotherapy, potentially via blocking protein binding to specific 3 0 UTRs with antisense oligonucleotides (Fei et al, 2017;Shen & Corey, 2018) Additionally, development of compounds for global or transcript-specific NMD enhancement may represent a novel and potentially widely applicable anti-cancer strategy. In contrast, the example of BCL2 provides a case in which increasing transcript sensitivity to NMD may provide therapeutic benefit.…”
Section: Discussionmentioning
confidence: 88%
“…). HNRNPL is mainly localized in the nucleus and participates in transcription, splicing, and processing of RNA . However, HNRNPL has cytoplasmic functions as well, including the regulation of vascular endothelial growth factor A translation …”
Section: Resultsmentioning
confidence: 99%
“…Importantly, we establish the CASC9 and HNRNPL interaction in HCC cells by the RAP and RIP methods. The interacting protein HNRNPL is a multifunctional RBP and involved in splicing, RNA stability, regulation of translation, and transcription . HNRNPL itself is an oncogenic protein and interacts with lncRNAs in different cancer types .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have systematically analyzed changes in lncRNA expression in macrophages upon innate immunity activation. These studies have shown that hnRNPL and linc1992 form an RNP complex that regulates transcription of tumor necrosis factor alpha (TNFα) by binding to the gene's promoter . Another study showed that as a coactivator of NF‐kB, lincRNA‐Cox2 functions as a regulator of the late phase of the primary immune response via modulation of epigenetic chromatin remodeling .…”
Section: Introduction Of Lncrnasmentioning
confidence: 99%